2009
DOI: 10.1021/jm900775q
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxamic Acids As a Novel Family of Serine Racemase Inhibitors: Mechanistic Analysis Reveals Different Modes of Interaction with the Pyridoxal-5′-phosphate Cofactor

Abstract: Mammalian serine racemase (SR) is a pyridoxal-5'-phosphate (PLP) dependent enzyme responsible for the biosynthesis of the neurotransmitter D-serine, which activates N-methyl-D-aspartate (NMDA) receptors in the CNS. Aberrant regulation of NMDA receptor signaling has been implicated in a variety of neuropathologies, and inhibitors of SR would therefore be a worthwhile tool for further investigation or treatment of such conditions. Here, we identify a series of small aliphatic hydroxamic acids (HAs) that act as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…[19][20][21][22][23][24][25] Although the involvement of SR in pathological conditions and its potential druggability has preliminarily been validated through genetic techniques, [25] very little is known about small molecule inhibitors. [13,[26][27][28] Naturally occurring amino acids, such as glycine or l-aspartate, have physiological significance as inhibitors, [26] presumably by modulating the biosynthesis of D-Ser (1). Sulfhydryl containing amino acids, [13,26] and amino acids b-substituted with electron withdrawing groups are also SR inhibitors, [13,26] which covalently bind PLP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25] Although the involvement of SR in pathological conditions and its potential druggability has preliminarily been validated through genetic techniques, [25] very little is known about small molecule inhibitors. [13,[26][27][28] Naturally occurring amino acids, such as glycine or l-aspartate, have physiological significance as inhibitors, [26] presumably by modulating the biosynthesis of D-Ser (1). Sulfhydryl containing amino acids, [13,26] and amino acids b-substituted with electron withdrawing groups are also SR inhibitors, [13,26] which covalently bind PLP.…”
Section: Introductionmentioning
confidence: 99%
“…The most potent inhibitors, with Ki in the low micromolar range, are malonic acid (3) [13] and l-erythro-3-hydroxyaspartate, [13] along with some members of a class of hydroxamic acids. [27] Central to the discovery of new, structurally diverse and tractable inhibitors is the availability of high resolution X-ray crystal structures of the target, which could help deciphering the molecular requirements for selective and potent inhibitors. Crystal structures of SR are available for the S. pombe [29,30] and, more recently, for rat [7] and human [7] enzymes (Table 1), which share more than 90 % sequence identity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Inoue and coworkers showed that amyloid-β-peptide mediated excitotoxicity is abrogated in SR knock-out mice 11 , providing compelling evidence for the potential utility of SR inhibitors as therapeutic agents. However, very few competitive SR inhibitors have been described to date, and the most potent of these have K i values in the micromolar range 12,13 .…”
mentioning
confidence: 99%
“…Even if the results are apparently discouraging, they are in line with data published so far, confirming that targeting SR is a strenuous challenge. Besides malonate, the most effective known inhibitors presenting inhibition constants in the micromolar range are the unselective L-erithrohydroxyaspartate and 2,2-dichloromalonate 40,41 . Other research groups tried to develop SR inhibitors starting from substrate analogues, yet with results similar to ours 40,42 .…”
Section: Discussionmentioning
confidence: 99%